Community life and governance : early experiences of Mnjikaning First Nation with Casino Rama ... - Campbell, Karen, 1971- (National Library of Canada, 1999)
Casino gambling offers large profits to support self-government and economic self-sufficiency for First Nations communities. Casinos also increase the number of problem gamblers, redistribute money from families with low and moderate incomes, and exacerbate community divisions and cultural conflicts. This qualitative study explores the experiences of Mnjikaning (Rama) First Nation, approximately one year after it opened the largest Native casino in Canada. Primary data are from fifty-three formal interviews, conducted from July to October 1997, and informal discussions between June 1994 and September 1998. The report focuses on how the casino affected community life and governance. Casino development gave Rama increased employment, new buildings and more social and administrative services. It has also been extremely disruptive, with increased traffic, many more strangers in the community, and a greater incidence of gambling problems among community members. The casino's considerable influence over ...